INVESTIGATION OF DIFFERENT CARBOHYDRATE SOLUTIONS ENHANCED THE VASE LIFE OF CUT CARNATION FLOWERS TION FLOWERS (Dianthus caryophyllus Dianthus caryophyllus L.) CVS. MASTER AND YELLOW CANDY - S. SUGANYA; J. PADMANABAN; M. KALAIMANI (The Bioscan, 2019)
The present investigation on the effect of different carbohydrate solutions on quality and vase life of cut carnation flowers (Dianthus caryophyllus L.) cvs. Master and Yellow Candy, was carried out during the years 2016-2017 at the laboratory of Department of Horticulture, Annamalai University. The different sources of carbohydrate such as sucrose, common sugar, palm sugar, palm crystals and karupatti each at 1, 3 and 5% was laid out in completely randomized design with 16 treatments including a control. The water, quality and vase life parameters were observed in both the cultivars. Holding of carnation flowers with sucrose 5% resulted in maximum CUW (23.86 and 22.49g flower-1), minimum CTLW (20.29 and 21.84g flower-1 respectively), maximum fresh weight (14.36 and 13.63g flower-1), highest diameter of the flower (7.70 cm and 7.44 cm), slowest stem strength (82.430 and 80.670) and with vase life of (5.87 and 5.76 days) as compared with (3.34 and 2.45 days) in control in both the cultivars. Among the different carbohydrates Sucrose 5% was found highly effective for longevity of carnation flowers.